2019
DOI: 10.3389/fmars.2018.00498
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton Taxonomic and Trophic Community Structure Across Biogeochemical Regions in the Eastern South Pacific

Abstract: Biochemical conditions and taxonomic composition of size-fractioned mesozooplankton were studied after a cruise conducted in September 2015 between the Chilean coast (70 • W) and Easter Island (110 • W) within the central south Pacific gyre. Taxonomy was assessed with an automated method based on image analysis and biochemical conditions assessed by analyses of C and N contents and stable isotope composition. Based on surface Chlorophyll-a levels, four regions were distinguished across the zonal gradient: eutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 67 publications
(80 reference statements)
6
22
0
Order By: Relevance
“…Figure 1 illustrates our study area and the sites from which zooplankton samples have been obtained and used in this study and information of the samples sources and data are summarized in Supplementary Table S1. González et al (2019) distinguished four ecological zones in this region, as based on the surface chlorophyll-a (Chla-a) concentration, from the highly productive upwelling area toward the central south Pacific gyre. This study found significant changes in zooplankton community structure among these zones, defined as: the CUP-Z, the coastal transition zone (CTZ), the oligotrophic zone (OLIGO-Z) and the ultra-oligotrophic zone (U-OLIGO-Z) which are illustrated in Figure 1.…”
Section: Study Area and Data Basesmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 illustrates our study area and the sites from which zooplankton samples have been obtained and used in this study and information of the samples sources and data are summarized in Supplementary Table S1. González et al (2019) distinguished four ecological zones in this region, as based on the surface chlorophyll-a (Chla-a) concentration, from the highly productive upwelling area toward the central south Pacific gyre. This study found significant changes in zooplankton community structure among these zones, defined as: the CUP-Z, the coastal transition zone (CTZ), the oligotrophic zone (OLIGO-Z) and the ultra-oligotrophic zone (U-OLIGO-Z) which are illustrated in Figure 1.…”
Section: Study Area and Data Basesmentioning
confidence: 99%
“…Biodiversity and species distribution of zooplankton are known to be affected by changes in oceanographic conditions, such as temperature, oxygenation, salinity and stratification, as it has been demonstrated in other regions of the world (Beaugrand et al, 2002;Beaugrand, 2003;Richardson and Schoeman, 2004;Peterson et al, 2006;Aronés et al, 2009;Gewin, 2010;Seibel, 2011), revealing the strong dependence of these organisms on oceanographic variables due to their limited migration capacity and so reflecting the strong effects of hydrographic patterns on their distribution and that of their prey (McClain and Barry, 2010). In this context, the Southeast Pacific (SEP) shows a great heterogeneity in hydrographic conditions from coastal to open sea gradient evidenced by a progressive increase of depth of the mixing layer, dissolved oxygen, temperature and surface salinity (Palma and Silva, 2006;González et al, 2019). Also, within the same gradient it is possible to observe drastic changes in biological productivity, which is high in the coastal zone (Humboldt Current) and extremely low in the ultraoligotrophic central gyre (Bonnet et al, 2008;Morel et al, 2010;Kletou and Hall-Spencer, 2012;Mann and Lazier, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zooplankton and other aquatic invertebrates play an essential role in the ecology of aquatic ecosystems (González et al, 2018). Some invertebrates are sensitive to changes in water quality and therefore are indicators of water quality (Berraho et al, 2019).…”
Section: Introductionmentioning
confidence: 99%